Dynamics of Magnetic Relaxation in Spheromaks - Garcia Martinez, Pablo Luis (2012)
The first attempts to get energy from the controlled fusion of two light atoms nuclei date back to the beginning of the fifties of the last century. The crucial difficulty to achieve this goal is that particles need to have a large amount of thermal energy in order to have a significant chance of overcoming the Coulomb repulsion. At such high temperatures the atoms are fully ionized conforming a plasma. Such a hot plasma can not be in contact with solid walls because it will be rapidly cooled down. Two main methods have been developed to confine plasmas: the magnetic confinement and the inertial confinement. Here we are concerned with the magnetic confinement approach. Under certain conditions some magnetic configurations studied in the context of plasma confinement become unstable and undergo a process called magnetic (or plasma) relaxation. This process generally causes the system to evolve toward a self-organized state with lower magnetic energy and almost the same magnetic helicity. A key physical mechanism that operates during plasma relaxation is the localized reconnection of magnetic field lines. It was demonstrated that magnetic relaxation can be employed to form and sustain configurations relevant to magnetic confinement research...